CONSTITUTIONAL COMPLAINTS AS EXTRAORDINARY LEGAL REMEDIES AGAINST VIOLATIONS OF CITIZENS CONSTITUTIONAL RIGHTS - Edy Suasono; Priyo Saptomo; Tri Dian Aprilsesa (PRANATA HUKUM, 2023)
Indonesia adheres to the doctrine of constitutionalism, thus the assurance of protection for citizens' constitutional rights needs to be implemented. Constitutional violations against citizens' rights currently lack extraordinary legal measures to address them. Therefore, the author analyzes the necessity of extraordinary legal measures (Constitutional Complaint) for ensuring the protection of citizens' constitutional rights. The author employs a normative legal research method with a normative juridical approach, collecting secondary and primary legal sources, including secondary and tertiary sources. The legal materials used consist of books, journals, scholarly works, articles, and relevant legal foundations. In this research, the primary legal foundation emphasized is the 1945 Constitution of the Republic of Indonesia. To analyze this data, a descriptive analysis technique is used by gathering references from various sources, aligning them with the used legal foundation, and then conducting an analysis. The results of this research indicate the necessity of granting Constitutional Complaint authority to the Constitutional Court to provide legal certainty and ensure the protection of the constitutional rights of justice seekers.